Environmental education and the challeng of socioenvironmental sustainability - Jacobi, Pedro (O Mundo da Saúde, 2006)
Developments towards a sustainable society are permeated by obstacles, as there is only a restricted societal conscience about the implications of the existing developmental model. Ecological predatory activities are attributable mainly to social institutions, to informational and communicational systems and to values adopted by society. The multiplication of risks of severe consequences, mainly environmental and technological ones, is a key element for understanding the characteristics, the limits and the transformations of modernity. Society as a producer of risks becomes increasingly reflexive, that is, it comes to be a theme and a problem in itself. Global reflexive society is urged to auto-confront itself with what it created, be it positive or negative. In this text, the considerations on “risk society” allow us to establish links with the complex theme that permeates the relations between environment and education, from some parameters present in practices oriented towards an “education for sustainability”, making ever more relevant the engagement of the various knowledge systems and the qualification of professionals and the academic community in an interdisciplinary perspective.